Development of Interactive E-Module Based on Heyzine Flipbook to Enhance Student Creativity in Basic Culinary Subjects - Ermy Rizky Barokah; Elida Elida; Kasmita Kasmita; Elfi Tasrif (STKIP Singkawang, 2025)
This study addresses the low level of creativity among students in designing menus in the Culinary Basics subject at SMK Negeri 3 Kota Solok. Observations revealed that students’ menu designs were monotonous, lacked innovation, and did not meet the Criteria for Achievement of Learning Objectives, due to limited teaching materials, conventional methods, and the absence of interactive media. The research aimed to develop an interactive e-module based on Heyzine Flipbook to improve students’ creativity in menu design. This Research and Development (R&D) study adopted the 4D development model (Define, Design, Develop, Disseminate) with Grade 10 Culinary Skills students as subjects. Product validity was assessed by material and media experts, practicality by teachers and students via questionnaires, and effectiveness by evaluating students’ creative products on novelty, problem-solving, and elaboration. Results showed the e-module to be valid (material expert score 0.92, media expert score 0.888), highly practical (teacher score 0.97, student score 0.89), and effective. The experimental class achieved a creativity score of 94.44 (highly effective) compared to the control class’s 63.80 (less effective). These findings confirm the e-module’s suitability as an engaging, effective learning medium supporting the implementation of the independent curriculum in vocational education